2017
DOI: 10.1080/20002297.2016.1274582
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus reuteri has antifungal effects on oral Candida species in vitro

Abstract: Background: An alternative approach for managing Candida infections in the oral cavity by modulating the oral microbiota with probiotic bacteria has been proposed. Objective: The aim was to investigate the antifungal potential of the probiotic bacterium Lactobacillus reuteri (DSM 17938 and ATCC PTA 5289) against six oral Candida species (C. albicans, C. glabrata, C. krusei, C. tropicalis, C. dubliniensis, and C. parapsilosis). Design: The lactobacilli were tested for their ability to co-aggregate with and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 41 publications
(58 reference statements)
4
64
1
1
Order By: Relevance
“…In a recent in vitro study, our group showed that L. reuteri (DSM 17938 and ATCC PTA 5289) inhibited the growth of C. albicans, C. dubliniensis, C. tropicalis, C. parapsilosis, and C. glabrata but not of C. krusei (Jorgensen et al, 2017), which supports the circumstance that one patient in the probiotic group with C. krusei at baseline developed OC after steroid treatment at Visit 2. All patients with OC were treated topically with nystatin oral mixture, which is a broadspectrum antimycotic drug with effect on all Candida species.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In a recent in vitro study, our group showed that L. reuteri (DSM 17938 and ATCC PTA 5289) inhibited the growth of C. albicans, C. dubliniensis, C. tropicalis, C. parapsilosis, and C. glabrata but not of C. krusei (Jorgensen et al, 2017), which supports the circumstance that one patient in the probiotic group with C. krusei at baseline developed OC after steroid treatment at Visit 2. All patients with OC were treated topically with nystatin oral mixture, which is a broadspectrum antimycotic drug with effect on all Candida species.…”
Section: Discussionsupporting
confidence: 61%
“…This might indicate that these patients harbor specific Candida strains that are more difficult to treat as there seems to be significant interspecies difference in terms of sensitivity to L. reuteri (DSM 17938 and ATCC PTA 5289). L. reuteri (DSM 17938 and ATCC PTA 5289) produces lactic acid and hydrogen peroxide and has the ability to co‐aggregate when exposed to Candida species in vitro, yet interspecies differences do exist (Jorgensen et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has investigated the effect of Lactobacilli reuteri ( L. reuteri ; DSM 17938 and ATCC PTA 5289) in vitro and in vivo on Candida ( C .) species (Jorgensen, Kragelund, Jensen, Keller, & Twetman, ; Kraft‐Bodi, Jorgensen, Keller, Kragelund, & Twetman, ). In 2014, it was discovered that Malassezia is a predominant oral fungus genus in the mouth and that the relative abundance varied between 13% and 98% in saliva samples from healthy individuals (Dupuy, David, Li, Heider, Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…8 This Candida is one of the normal flora found in the oral cavity in 25-75% of the population, and it also can be found in the human gastrointestinal tract. 9,10 This species has the characteristics of an opportunistic pathogen: it is harmless in healthy individuals, but under certain conditions, it can cause infection in the oral cavity. 10,11 The infection can be caused by a hormone imbalance, antibiotic overuse, long term use of immunosuppressants, and the ability of C. albicans to change into an invasive form.…”
Section: Introductionmentioning
confidence: 99%